Critical thinking credibility - Taylor, Steve; Blakemore, Ken.; Online Classroom (Bendigo, Vic. : Video Education Australasia [distributor], 2009)
What is credibility, and why is it so important? This program begins with an exploration of the concept of credibility and illustrates the key criteria of motive, bias, vested interest, neutrality, ability to perceive and expertise. A reconstruction of a famous murder case from the 1920s is then used to provide the material for viewers to evaluate the credibility of the evidence that was used. Finally, critical thinking author and former chief examiner Dr. Roy van den Brink Budgen provides his analysis of the case study and follow up support material. A very credible resource about credibility
DVD format.
System requirements : progressive scan DVD player.
Keywords: Identity (Psychology) -- Social aspects